2006
DOI: 10.1016/j.yjmcc.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential cardiotoxic/cardioprotective effects of β-adrenergic receptor subtypes in myocytes and fibroblasts in doxorubicin cardiomyopathy

Abstract: beta-Adrenoceptor (beta-AR) subtypes act through different signaling pathways to regulate cardiac function and remodeling. Previous in vivo data show a markedly enhanced cardiotoxic response to doxorubicin in beta2-/- mice, which is rescued by the additional deletion of the beta1-AR. We determined whether this differential response was myocyte specific by examining the effects of doxorubicin in myocytes and fibroblasts from WT and beta1, beta2 and beta1/beta2-/- mice. Cells were exposed to doxorubicin at 1-50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…But besides the fact that the observed effect is likely to be different according to the model and the condition, it has been described that the relationship between ADRB stimulation and apoptosis depends upon ADRB subtype. For example, Fajardo et al [48] have described that ADRB2 appears to play a cardioprotective role, whereas ADRB1 plays a cardiotoxic role. Moreover, it has been shown that blocking ADRB pathway with propranolol, a selective antagonist, in septic mice increased the splenocyte apoptosis rate [49] and that, on the contrary, the use of isoproterenol, a nonselective ADRB1, ADRB2, and ADRB3 agonist, decreased apoptosis of T-cell subtype [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But besides the fact that the observed effect is likely to be different according to the model and the condition, it has been described that the relationship between ADRB stimulation and apoptosis depends upon ADRB subtype. For example, Fajardo et al [48] have described that ADRB2 appears to play a cardioprotective role, whereas ADRB1 plays a cardiotoxic role. Moreover, it has been shown that blocking ADRB pathway with propranolol, a selective antagonist, in septic mice increased the splenocyte apoptosis rate [49] and that, on the contrary, the use of isoproterenol, a nonselective ADRB1, ADRB2, and ADRB3 agonist, decreased apoptosis of T-cell subtype [50].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in an exploratory analysis we assessed time trend for CASP3 mRNA expression (3,6,12,48, and 72 h) and found that the peak for mRNA expression occurred around 3 h of stimulation (in fold increase compared with controls: 8.6, 6.1, 2.3, 2.1, and 1.2, at 3 h, 6 h, 16 h, 48 h, and 72 h, respectively).…”
Section: Chorioamnionitis Is Associated With Apoptosis In Human Myomementioning
confidence: 99%
“…In animal models of doxorubicin-induced cardiomyopathy, β2 receptor-deficient mice develop severe and lethal acute cardiotoxicity, and the additional deletion of the β1 receptor rescues this completely. 18 Thus, in animals exposed to anthracyclines, β1 activation seems to be cardiotoxic, whereas β2 activation is cardioprotective. The cardioprotective effect of β2 receptor activation seems to be mediated, in part, via activation of prosurvival kinases and a decrease in the intracellular concentration of calcium, thus attenuating the mitochondrial dysfunction seen with anthracyclines.…”
Section: Are All β-Blockers Equally Cardioprotective?mentioning
confidence: 99%
“…96 Similar conclusions were derived from experiments with isolated murine cardiomyocytes. 97 However, other studies indicate that ␤-blockade alone might not provide sufficient cardioprotection against anthracycline cardiotoxicity. Oxidative stress, mitochondrial dysfunction, and histopathological lesions induced by anthracyclines in a rat heart were inhibited by carvedilol, an ␣-␤-blocker with some antioxidant properties.…”
Section: Beta-adrenergic Blockersmentioning
confidence: 99%